POTENSI PENYU HIJAU (Chelonia mydas L.) DAN PEMANFAATANNYA SEBAGAI DAYA TARIK WISATA DI KAWASAN PANTAI SINDANGKERTA, KABUPATEN TASIKMALAYA - Reni Sri Mulyaningsih; Agus Priyono; Eva Rachmawati (Department of Forest Resources Conservation and Ecotourism - IPB University, 2010)
Sindangkerta beach is one of the spreading locations of green turtles (Chelonia mydas L.) in Indonesia. The existence of the green turtles can potentially and utilization as one of the ocean ecotourism objects. The purpose of the research is investigating the potential and utilization of green turtles such as environment, habit, spreading of nest, and laying eggs period as one of the ocean ecotourism. Development of green turtle potency as one of the ocean tourism is process of lay eggs and behavior of feeding hunt. Keywords :Chelonia mydas, Sindangkerta, ecotourism